The Influence of Career Development and Work Environment on Employee Performance: A literature review - Lustari, Ambar; Isnanto, Samto Hadi (Dinasti International Journal of Management Science, 2025)
The purpose of this article is to determine whether Career Development and Work Environment affect Employee Performance. The method used in this study is a research method with a literature study sourced from open access electronic journals. The analysis uses qualitative descriptive. The results obtained indicate that: 1) Career Development affects Employee Performance; 2) Work Environment affects Employee Performance. This study is a literature study of various previous studies that are considered relevant, so that they can be used as reference material for further research in the field of human resources in determining the company's management strategy.